Urgency and Challenges of Illicit Enrichment Regulation in the Draft Law on Asset Forfeiture in Indonesia - Putra Andika; Suparji Ahmad; Anis Rifai (Universitas Muhammadiyah Purwokerto, 2024)
The enforcement of laws regarding illicit enrichment, as part of the effort to combat corruption, presents a significant challenge in many countries. Commitment to preventing this crime involves the enactment of legislation that criminalizes illicit enrichment and prescribes criminal penalties. The importance of passing the Asset Forfeiture Bill and enhancing the AntiCorruption Law, including provisions addressing illicit enrichment, is paramount. The objective of this research is to underscore the significance of incorporating provisions on illicit enrichment in the Asset Forfeiture Bill as a solution to economic crimes, particularly those involving public officials unable to account for the origins of their wealth. The research methodology employed is normative legal research with three approaches: legislative analysis, conceptual analysis, and comparative analysis. The research findings indicate that regulations concerning illicit enrichment require improvement to consider the principle of equality before the law, particularly the rights of the accused in court. Without such considerations, the implementation of the Asset Forfeiture Bill can be susceptible to abuse and may not act as a deterrent for public officials to avoid economic crimes. Some officials have also exploited legal loopholes within these regulations. To enhance its effectiveness, amendments, and refinements to the Asset Forfeiture Bill are necessary to address these weaknesses. This will help establish a fair legal system, prevent the abuse of power by public officials, and improve the effectiveness of combating corruption and economic crimes that harm the state.Keywords: Illicit enrichment, Corruption Criminal Act, Asset Forfeiture.